Reserve Components as a Non-Military Defense Strategy to Support Defense Economic - Asmara, Johar; Saputro, Guntur Eko; Prakoso, Lukman Yudho (Yayasan Sembilan Pemuda Indonesia, 2023)
Indonesia has large human resources and has a lot of potential if proper management and development is carried out. Human resources are the most important aspect as a determinant of the development of national defense. This potential has a positive effect with the aim of forming a reserve component as a support for national defense forces so that the formation of this reserve component can also be interpreted as a strategy. This paper aims to explain how the role of reserve components in non-military defense efforts. The method used by researchers is a qualitative method with a literature study approach. The result of this writing is that the reserve components originating from the community will return to the community, then this is considered as a soft-approach strategy to form a nationalist youth generation which will ward off threats that arise from various aspects of social life. It is hoped that the development of the strength and capability of national defense in the management of the reserve component will result in the success of the universal people’s security and defense system with a large number of civil society members becoming members of the reserve component.